2015
DOI: 10.1038/srep07624
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity strain sensor based on in-fiber rectangular air bubble

Abstract: We demonstrated a unique rectangular air bubble by means of splicing two sections of standard single mode fibers together and tapering the splicing joint. Such an air bubble can be used to develop a promising high-sensitivity strain sensor based on Fabry-Perot interference. The sensitivity of the strain sensor with a cavity length of about 61 μm and a wall thickness of about 1 μm was measured to be up to 43.0 pm/με and is the highest strain sensitivity among the in-fiber FPI-based strain sensors with air cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 23 publications
0
64
2
1
Order By: Relevance
“…For the device samples with cavity length of ~20 μm, the crescent shaped FP cavity has a visibility of 7 dB, compared with the results of 5 and 6.5 dB of the D-shaped and elliptic FP cavities with cavity length of ~24 μm. It can also be noted that the thickness of cavity wall plays no clearly significant role when compared with the cavity length, being different from that of the previous work reported20. This is likely due to the fact that our device samples exhibit only a short length of cavity wall (at least one reflection surface is a curve) associated with a relatively large thickness.…”
Section: Resultscontrasting
confidence: 77%
“…For the device samples with cavity length of ~20 μm, the crescent shaped FP cavity has a visibility of 7 dB, compared with the results of 5 and 6.5 dB of the D-shaped and elliptic FP cavities with cavity length of ~24 μm. It can also be noted that the thickness of cavity wall plays no clearly significant role when compared with the cavity length, being different from that of the previous work reported20. This is likely due to the fact that our device samples exhibit only a short length of cavity wall (at least one reflection surface is a curve) associated with a relatively large thickness.…”
Section: Resultscontrasting
confidence: 77%
“…According to Equation (3), it can be found that λ is directly proportional to L . As the ultrasonic pressure is applied to the FP-based interferometer [21,22,23], it will introduce a strain along the fiber, stretching the air bubble periodically. Thus, the cavity length of the interferometer increases with the ultrasonic pressure application.…”
Section: Sensor Fabrication and Operation Principlementioning
confidence: 99%
“…The FPI strain sensor of the air bubble was fabricated by two standard SMF and formed by arc fusion splicing; Chongqing University’s experimental results showed the strain sensitivity to be ~4 pm/με [15]. Shenzhen University reported a high-sensitivity of up to 6.0 pm/με [16], and then they improved the technique to create a rectangular air bubble based FPI with a cavity length of about 61 μm; the wavelength of 1550 nm exhibits a high strain sensitivity of 43.0 pm/με [17]. …”
Section: Introductionmentioning
confidence: 99%